Malaysian ethnic festival foods, its food ways and the young generation practices / Rosmaliza Muhammad - Muhammad, Rosmaliza (2011)
Malaysia is recognized as one of the unique country through it multi-ethnic populations which consist of Malays, Chinese, Indians and other Indigenous groups. Each ethnic besides language, belief and religion, has their own cuisine and food culture practices. Similar to other nations, food and beverages for every ethnic in this country either for daily consumes and special occasions were created by earlier generations using the natural resources or any consumable things available during their era. Food and beverages in fact have long been an important element for every ethnic festival with various cooking methods, equipments and eating decorum. The vast of the ethnic festival foods treasures however are believed to have some transformation or alteration due to the waves of modernization. This study empirically examines the extent of modernization influences Malaysian ethnic festival foods and foodways. Some meaningful insights related to the issues of interest were obtained by using semi structured interviews with selected influential individuals among the three major ethnics groups (Malays, Chinese and Indians). Modernization through the elements of technology, commercialization and social advancement without doubt has slightly altered not only on daily food but also to Malaysian ethnic festival food. The alterations not only involve the preparation which relates to the ingredients, equipments and cooking methods but also entail the consumption of it through the modern eating decorum including utensils and serving styles. The commercialization of ingredients and increasing of convenience foods products without exception of festival delicacies, the emergence of technological advancement in cooking equipments and utensils, social advancement through economic factors, educational level and lifestyle directly contribute to the alteration processes. However without realizing and despite many advantages, the wave of modernization also somehow creates the negative impacts although not as many of the benefits. The integrative force, solidarity, alliances, togetherness, kinship and interaction that have long been practiced by the ethnic family members and community for the festival food preparation are also lessened. The most significant impact of this study is on the young generation as they begin less interested, less able, could not care less and disregard the tradition particularly in the festival food practices. If this situation continuously happened without any efforts undertaken, sooner or later the traditional way of preparing ethnics food treasures will totally disappeared. Therefore, some proactive actions should be taken. Thus, some necessary action therefore must be taken by the individuals, community as well as the government.